Glutamatergic Receptors Modulate Normoxic but Not Hypoxic Ventilation and Metabolism in Naked Mole Rats - Dzal, Yvonne A.; Seow, Allison; Borecky, Lisa G.; Chung, Danielle; Gill, Sharn K. G.; Milsom, William K.; Pamenter, Matthew E. (Frontiers in Physiology, 2019)
Naked mole rats (Heterocephalus glaber) are among the most hypoxia-tolerant mammals, but their physiological responses to acute and chronic sustained hypoxia (CSH), and the molecular underpinnings of these responses, are poorly understood. In the present study we evaluated the acute hypoxic ventilatory response, and the occurrence of ventilatory acclimatization to hypoxia following CSH exposure (8-10 days in 8% O2) of naked mole rats. We also investigated the role of excitatory glutamatergic signalling in the control of ventilation and metabolism in these conditions. Animals acclimated to normoxia (control) or CSH and then exposed to acute hypoxia (7% O2 for 1 hr) exhibited elevated tidal volume (VT), but decreased breathing frequency (fR). As a result, total ventilation (V ̇E) remained unchanged. Conversely, VT was lower in CSH animals relative to controls, suggesting there is ventilatory plasticity following acclimatization to chronic hypoxia. Both control and CSH-acclimated naked mole rats exhibited similar 60-65% decreases in O2 consumption rates during acute hypoxia, and as a result their air convection requirement increased 2.4 to 3-fold. Glutamatergic receptor inhibition decreased fR, V ̇E, and O2 consumption rates in normoxia but did not alter these ventilatory or metabolic responses to acute hypoxia in either the control or CSH groups. Taken together, these findings indicate that ventilatory acclimatization to hypoxia is atypical in naked mole rats, and glutamatergic signalling is not involved in their hypoxic ventilatory or metabolic responses to acute or chronic hypoxia.